Household Food Security: Evidence From South Sumatera - Azwardi, Azwardi; Widyasthika, Hayu Faldun; Saleh, Rosmiyati Chodijah; Adnan, Nazeli (JEJAK: Jurnal Ekonomi dan Kebijakan, 2019)
This study aims to determine the phenomenon of food security in South Sumatra Province. Food security is calculated using Shortfall/Surplus Index and Head Count Ratio. Binary Logistic Regression method is used to determine factors affecting food security. This study obtains data from National Socio-Economic Survey on March 2017 regarding average number of calories consumed by household per day, socio-economic characteristics of household, and household heads in South Sumatra. The Survey used total sample of 9,752 households consisting of 3,099 urban households and 6,653 rural households. The results of the study shows that using 2,100 kcal standard limit, most of districts in South Sumatra have entered safe food security limit. However, they have not entered safe food security limit using 2,500 kcal standard limit. Factors that affect household food insecurity in South Sumatra Province are caused by the number of household members and the education of household heads.